ANTIBACTERIAL ACTIVITY OF SEAGRASS EXTRACT Enhalus acoroides WITH DIFFERENT SOLVENTS AGAINST Streptococcus mutans BACTERIA CAUSE DENTAL CARIES - Firman, Firman; Rieuwpassa, Fredrik; Mailoa, Meigy Nelce (Universitas Pattimura, 2024)
Treatment of Streptococcus mutans infection is generally done using antibiotics or chemical mouthwash, but long-term use can cause bacterial resistance and side effects for health. Therefore, it is important to find alternative treatments that are safer and more effective, one of which is through the use of medicinal plants. One plant that has potential as a source of antibacterial compounds is seagrass (Enhalus acoroides), which has been recognized in various studies to contain bioactive compounds such as flavonoids, saponins, and tannins, which can function as antibacterial agents. The purpose of this study was to determine the antibacterial activity of E. acoides extracts extracted with different solvents against S. mutans bacteria. The design used in this study is a completely randomised design (CRD) model. Testing the inhibition zone of E. acoroides using piper disc diffusion method with different concentrations of 25%, 50%, 75% and 100% with three replicates. Inhibitory zone diameter data were analyzed used ANOVA significant test and differences between treatments, and test of Real Honest Differences (BNJ) was conducted. Methanol and ethyl acetate extracts of E. acoroides can inhibit the growth of S. mutans bacteria that cause dental caries, and ethyl acetate has a stronger effect than methanol at higher concentrations.